Comment on “Tectonics of the Isua Supracrustal Belt 1: P-T-X-d Constraints of a Poly-Metamorphic Terrane” by A. Ramírez-Salazar et al. and “Tectonics of the Isua Supracrustal Belt 2: Microstructures Reveal Distributed Strain in the Absence of Major Fault Structures” by J. Zuo et al. - Nutman, A. P.; Friend, C. R.L.; Bennett, V. C. (Tectonics, 2022)
The two Isua supracrustal belt area (Greenland) papers by Zuo et al. (2021, https://doi.org/10.1029/2020tc006514) and Ramírez-Salazar et al. (2021, https://doi.org/10.1029/2020TC006516) contain no evidence supporting an Eoarchean “heat-pipe” geodynamic regime and yet no evidence negating a mobile lid one. From quartz micro-fabric studies, Zuo et al. (2021, https://doi.org/10.1029/2020tc006514) argued for Eoarchean “relatively equal strain distributed across the belt.” This contradicts clear meso- and macro-scale evidence for strongly heterogeneous Eoarchean deformation before the later deformed and metamorphosed ∼3,500 to 2,750 Ma Ameralik dykes were intruded. The Zuo et al. strain indicators relate to syn-amphibolite facies Neoarchean basin and dome formation throughout the ∼250 km extent of the Eoarchean gneiss complex. Ramírez-Salazar et al. (2021, https://doi.org/10.1029/2020TC006516) argued the Isua area's metamorphic signature reflects a uniform Eoarchan “heat-pipe” geodynamic regime. However, observed Eoarchean tectonothermal conditions are more diverse, including ultra-high-pressure relicts in peridotite lenses with supra-subduction zone attributes, and are incompatible with a “heat-pipe” regime.